Foam rolling for recovery: examining Doms reduction in recreational versus competitive athletic populations - Kong, Jona Zong Na (2024)
Background and Objective: Foam rolling, a type of massage therapy, has shown potential to alleviate delayed-onset muscle soreness (DOMS) induced by intense exercise. However, its effects on recreational versus competitive athletes remain underexplored. This study aims to investigate the effects of foam rolling on DOMS-related pain in recreational and competitive athletes.